Efficiency and Equity Implications of Alternative Instruments to Reduce Carbon Leakage - Christoph Böhringer; Jared C. Carbone; Thomas F. Rutherford (University of Oldenburg, Department of Economics, 2012)
The cost-effectiveness of unilateral emission abatement can be seriously hampered by emission leakage. We assess three widely-discussed proposals for leakage reduction targeted at energy-intensive and trade-exposed industries: border tax adjustments, output-based allocation and industry exemptions. We find that none of these measures amounts to a "magic bullet" when both efficiency and equity criteria matter. Border tax adjustments reduce leakage and provide global cost savings but exacerbate regional inequality. Exemptions produce very little leakage reduction and run the risk of increasing efficiency cost of climate policy. Output-based allocation does no harm but also does relatively little good by our outcome measures.
Keywords: 330; Unilateral Climate Policy; Leakage; Efficiency; Equity; Klimaschutz; Treibhausgas-Emissionen; Internationale Wirtschaft; Internationales Umweltrecht; Kosten-Wirksamkeits-Analyse; Gerechtigkeit; Theorie; Welt